METHODOLOGICAL STEPS FOR IMPLEMENTING INTERNATIONAL STANDARDS IN AGRICULTURAL ACCOUNTING (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Agriculture is a key sector of Uzbekistan’s economy, contributing significantly to food security, employment, and export revenues. However, the alignment of agricultural accounting practices with International Financial Reporting Standards (IFRS) remains a challenge. This study focuses on the adoption of IFRS, particularly IAS 41 (“Agriculture”), to improve the transparency, reliability, and international comparability of financial reporting in agricultural enterprises. The research evaluates the current state of financial reporting in Uzbekistan’s agricultural sector, identifies challenges in implementing IFRS, and proposes practical solutions to address these challenges.